Assessment of Mangrove Health in Pancer Cengkrong, Trenggalek, East Java, Indonesia - Diana Arfiati; Umi Zakiyah; Endang Yuli Herawati; Titis Dwi Andhani; Pratama Diffi Samuel; Sri Sudaryanti; Michelle Sylvanya Ivanney Sundalangi; Firuliza Nurus Sofi (Jurnal Kelautan Tropis, 2026)
Mangrove forests are highly sensitive to environmental disturbances, making them vulnerable to a decline in their condition and ecological functions. This study aims to assess the health of mangrove forests in Pancer Cengkrong, Trenggalek, using the mangrove health index method to support conservation and sustainable management efforts. The study was conducted from May to July 2025, using a survey method at six locations. The parameters studied were stem diameter (Sd), canopy cover (Sc), and sapling density (SNsp). This study identified 12 mangrove species, consisting of 11 true mangrove species, including Avicennia alba, Sonneratia alba, Avicennia marina, Rhizophora mucronata, Rhizophora apiculata, Achantus ilicifolius, Ceriops decandra, Derris trifoliata, Nypa fruticans, Excoecaria agallocha, as well as one associated mangrove species, Acrostichum speciosum. The highest species density was found in Rhizophora mucronata (6,075 ind.ha⁻¹), while the lowest was in Bruguiera gymnorrhiza (75 ind.ha⁻¹). SNsp values ranged from 4.10 to 4.12, Sd values ranged from 3.3 to 4.84, and Sc values ranged from 6.59 to 7.59. The health condition of the mangrove forest was categorized as “Moderate,” with the highest MHI at Site 1 (54.41%) and the lowest at Site 5 (48.34%). The “Moderate” mangrove forest health category indicates the need to limit activities that could cause degradation and damage, and to increase mangrove forest rehabilitation efforts to preserve a sustainable ecosystem.